Parenchymal-sparing Hepatectomy in Colorectal Liver Metastasis Improves Salvageability and Survival. Issue 1 (January 2016) - Mise, Yoshihiro; Aloia, Thomas A.; Brudvik, Kristoffer W.; Schwarz, Lilian; Vauthey, Jean-Nicolas; Conrad, Claudius
Abstract : Objective: To investigate prognostic impact of parenchymal-sparing hepatectomy (PSH) for solitary small colorectal liver metastasis (CLM). Background: It is unclear whether PSH confers an oncologic benefit through increased salvageability or is a detriment through increasing recurrence rate. Methods: Database of 300 CLM patients with a solitary tumor (⩽30 mm in size) was reviewed from 1993 to 2013. A total of 156 patients underwent PSH and 144 patients underwent right hepatectomy, left hepatectomy, or left lateral sectionectomy (non-PSH group). Results: The rate of PSH increased over the study period ( P  < 0.01). PSH did not impact negatively on overall (OS), recurrence-free, and liver-only recurrence-free survival, compared with non-PSH ( P  = 0.53, P  = 0.97, and P  = 0.69, respectively). Liver-only recurrence was observed in 22 patients (14%) in the PSH and 25 (17%) in the non-PSH group ( P  = 0.44). Repeat hepatectomy was more frequently performed in the PSH group (68% vs 24%, P  < 0.01). Subanalysis of patients with liver-only recurrence revealed better 5-year overall survival from initial hepatectomy and from liver recurrence in the PSH than in the non-PSH group [72.4% vs 47.2% ( P  = 0.047) and 73.6% vs 30.1% ( P  = 0.018), respectively]. Multivariate analysis revealed that non-PSH was a risk of noncandidacy for repeat hepatectomy (hazard ratio: 8.18, confidence interval: 1.89–45.7, P  < 0.01). Conclusions: PSH did not increase recurrence in the liver remnant but more importantly improved 5-year survival in case of recurrence (salvageability). PSH should be the standard approach to CLM to allow for salvage surgery in case of liver recurrence.